Asking for Panel Consent in Web Surveys: Choice, Opt-in, or Opt-out? - Oliver Lipps; Lukas Lauener; Anke Tresch (Survey Research Methods, 2025)
Some surveys ask respondents for consent to be recontacted for follow-up surveys after the initial  part of the survey has been completed. Based on an experiment, we compare three options for asking for this panel consent: choice (yes/no), opt-in, and opt-out. We analyse panel consent rates and compare consenters with non-consenters against a comprehensive set of socio-demographic characteristics, political attitudes, and survey-related variables in a probability-based web survey. In a second step, we analyse consenters’ actual participation in the first follow-up wave.